Axin1: A novel scaffold protein joins the antiviral network of interferon. Issue 6 (5th November 2022) - Guo, Yujie; Bamunuarachchi, Gayan; Vaddadi, Kishore; Zhu, Zhengyu; Gandikota, Chaitanya; Ahmed, Kainat; Pushparaj, Samuel; More, Sunil; Xiao, Xiao; Yang, Xiaoyun; Liang, Yurong; Mukherjee, Sanjay; et al.
Abstract: Acute respiratory infection by influenza virus is a persistent and pervasive public health problem. Antiviral innate immunity initiated by type I interferon (IFN) is the first responder to pathogen invasion and provides the first line of defense. We discovered that Axin1, a scaffold protein, was reduced during influenza virus infection. We also found that overexpression of Axin1 and the chemical stabilizer of Axin1, XAV939, reduced influenza virus replication in lung epithelial cells. This effect was also observed with respiratory syncytial virus and vesicular stomatitis virus. Axin1 boosted type I IFN response to influenza virus infection and activated JNK/c‐Jun and Smad3 signaling. XAV939 protected mice from influenza virus infection. Thus, our studies provide new mechanistic insights into the regulation of the type I IFN response and present a new potential therapeutic of targeting Axin1 against influenza virus infection. Abstract : In this study, we have discovered that the host protein Axin1 boosts host immunity in response to influenza virus infection. The finding presents a new potential therapeutic of targeting Axin1 against influenza virus infection.